1993
DOI: 10.1007/bf00203609
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and localization of plant phenolics likely involved in the pathogen resistance expressed by endomycorrhizal roots

Abstract: Abstract. Phytochemical characterization of the major phenolic compounds and their ultrastructural localization were carried out on onion roots (Allium cepa L.) colonized by two vesicular-arbuscular mycorrhizal (VAM) fungi: Glomus intraradix Schenck & Smith and G. versiforme (Karst.) Berch. Free and wall-bound forms of phenolic components were quantified in relation to the duration of symbiosis. Both ferulic and pcoumaric acids, as well as N-feruloyltyramine were identified as the major phenolic metabolites bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 23 publications
(25 reference statements)
2
46
0
1
Order By: Relevance
“…This is in contrast to pathogenic plant-fungus interactions, in which fungus-induced increased phenolic levels of the cell wall may constitute a barrier against pathogen invasion (Graham and Graham, 1991;Beimen et al, 1992;Kauss et al, 1993) by decreasing the digestibility of the cell wall (Fry, 1986). On the other hand, it has been observed that the levels of cell wallbound ferulic and 4-coumaric acids as well as a ferulic acid tyramine amide increase during mycorrhization of Allium cepa with G. intraradices and G. versiforme (Grandmaison et al, 1993). This may lead to an increased resistance of mycorrhizas to pathogenic fungi.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to pathogenic plant-fungus interactions, in which fungus-induced increased phenolic levels of the cell wall may constitute a barrier against pathogen invasion (Graham and Graham, 1991;Beimen et al, 1992;Kauss et al, 1993) by decreasing the digestibility of the cell wall (Fry, 1986). On the other hand, it has been observed that the levels of cell wallbound ferulic and 4-coumaric acids as well as a ferulic acid tyramine amide increase during mycorrhization of Allium cepa with G. intraradices and G. versiforme (Grandmaison et al, 1993). This may lead to an increased resistance of mycorrhizas to pathogenic fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this idea, HCAA are synthesized in the cytosol and transported into the cell wall, where they undergo peroxidative polymerization (Negrel and Martin, 1984;Negrel and Jeandet, 1987;Negrel and Lherminier, 1987;Negrel et al, 1993). The accumulation of HCAA in the cell wall creates a resilient barrier against pathogens by reducing cell wall digestibility and/or by directly inhibiting the growth of fungal hyphae (Grandmaison et al, 1993). Accordingly, the synthesis of HCAA is induced in response to various stresses, including physical injury, pathogen infection, and elicitor treatment.…”
mentioning
confidence: 86%
“…Induction of ferulic acid in mycorrhizal roots has been previously reported. 18 Remarkably, ferulic acid may be induced by fungal elicitors and jasmonates. 19,20 Our previous analysis pointed to jasmonates and related compounds as key regulators on the changes associated to the symbiosis in tomato, 13 and this may be the case also with ferulic acid levels.…”
mentioning
confidence: 99%